Celebrity appearance-shaming: Innocent bashing forms or reconfirming gender norms? A study into the explanations of adolescents’ celebrity appearance-shaming intentions - Gaëlle Ouvrein (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2023)
Celebrities regularly become victims of online body- and slut-shaming. This study refers to these practices as appearance-shaming and investigates potential explanations for adolescents’ intentions to participate in this behavior by means of an extended version of the theory of planned behavior (TPB). Apart from the three paths of attitudes toward the practice, subjective norms about the practice, and perceived behavioral control to participate in it, we added sexism as a potential variable to explain celebrity appearance-shaming. Through this addition, we were better able to capture the role of cultural background variables, something that was not included in the traditional elements of the TPB but appeared to be important for explaining normative behaviors. Based on a survey study of 248 adolescents (N = 248), we concluded that the TPB is a good theoretical framework for explaining intentions toward celebrity appearance-shaming. More specifically, having more accepting attitudes toward celebrity bashing, more supportive descriptive norms about celebrity bashing, and higher perceived behavioral control were associated with higher intentions. Moreover, sexism had a strong positive relationship with the intention to celebrity appearance-shaming. Participating in celebrity appearance-shaming might, in that way, be an indicator of strong traditional sexist beliefs and might contribute to keeping them alive among adolescents.